2020
DOI: 10.1016/s1473-3099(19)30410-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying risks and interventions that have affected the burden of lower respiratory infections among children younger than 5 years: an analysis for the Global Burden of Disease Study 2017

Abstract: Background Despite large reductions in under-5 lower respiratory infection (LRI) mortality in many locations, the pace of progress for LRIs has generally lagged behind that of other childhood infectious diseases. To better inform programmes and policies focused on preventing and treating LRIs, we assessed the contributions and patterns of risk factor attribution, intervention coverage, and sociodemographic development in 195 countries and territories by drawing from the Global Burden of Diseases, Injuries, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
91
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(95 citation statements)
references
References 38 publications
3
91
0
1
Order By: Relevance
“…suggests that the increased risk of ARI in children depends on a range of factors, including sub-optimal breastfeeding, malnutrition, household environment (such as crowding and air pollution), poor vaccine coverage and antibiotic misuse [57][58][59][60]. Consistent with the literature, our findings showed that children who commenced breastfeeding within the first hour of birth and were exclusively breastfed had a reduced risk of experiencing ARI compared to their counterparts.…”
Section: Plos Onesupporting
confidence: 87%
See 1 more Smart Citation
“…suggests that the increased risk of ARI in children depends on a range of factors, including sub-optimal breastfeeding, malnutrition, household environment (such as crowding and air pollution), poor vaccine coverage and antibiotic misuse [57][58][59][60]. Consistent with the literature, our findings showed that children who commenced breastfeeding within the first hour of birth and were exclusively breastfed had a reduced risk of experiencing ARI compared to their counterparts.…”
Section: Plos Onesupporting
confidence: 87%
“…Since 1990, despite substantial declines in global child mortality, respiratory infections still remain leading causes of death among children younger than five year of age [57]. Evidence Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…During our study, severe pneumonia was more common in children between two and 12 months of age compared with children between 13 and 60 months of age. The global prevalence of pneumonia is highest in the age group of 1-4 years [18]. Children residing in rural areas were more affected with severe pneumonia compared with children living in urban areas, and the condition showed a marked male predilection.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from low/middle-income countries (LMICs) have tried to identify the risk factors for severe pneumonia [6][7][8][9][10][11][12][13][14][15][16][17], but only a few studies from India have reported the risk factors for severe pneumonia [6,8,13]. More clinical studies from India are needed as the country alone contributes to 32% of the annual global burden of pediatric pneumonia [18]. India had the highest number of global U-5 deaths due to pneumonia with an estimated 508 deaths per day in 2017 [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation